Family history and identity in São Paulo - Lang, Alice Beatriz da Silva Gordo; Marcondes, Nilce (Cadernos CERU, 1999)
The paper deals with family group conceived as representation. It was based in a research intending to know how people of different social classes see family group, and to point its role in the building ofpersonal identity in São Paulo - Brazil. The study was based in life stories of women and their accounts point to the existence of private life styles determined by social origin. Members of the upper social class tend to base their personal and social identitiy on their extensive farnily whose history is seen and cultivated as a myth. On the opposite, in the middle and popular classes, the family group pointed is the nuclear one, the family history is build in the present, and the personal identity has its basis in the occupational trajectory of the individual itself.